Literature Review: Group Guidance Techniques to Reduce Public Speaking Anxiety - Yuliska Putri, Fharoza; Nurwahidin, M.; Rahmayanthi, Ranny (UNDIKMA, 2024)
The occurrence of anxiety in public speaking can occur anywhere and to anyone. The problem that often arises at this time, the tendency of a person will experience anxiety when talking about something in a crowd that is influenced by the person himself. The current problem in schools in Bandar Lampung, a student will tend to feel depressed if the teacher asks him to perform in front of the class, the student will feel threatened if he gets a question directed at him. For this reason, this research seeks to explain group guidance techniques to reduce public speaking anxiety in literature. This research uses the SLR Method used to identify, review, evaluate, and interpret all available research with the topic area of the phenomenon of interest. The results showed that group guidance techniques are effective in reducing public speaking anxiety. Through this technique, individuals can identify the causes of their anxiety, learn coping strategies, and gain support from group members. This can increase confidence in public speaking and reduce anxiety symptoms. Thus, the Group Guidance Technique can be an effective approach in helping individuals overcome public speaking anxiety.